Moderating Factors in the Path from Physical Abuse to Attempted Suicide in Adolescents: Application of the Interpersonal‐Psychological Theory of Suicide. Issue 3 (5th February 2013) - Cero, Ian; Sifers, Sarah
<x xml:space="preserve">Abstract</x> Childhood physical abuse is a major risk factor for suicide attempt, but factors that moderate this risk remain largely unexamined. Moderated mediation analysis was used with 186 adolescents who responded to the Profiles of Student Life: Attitudes and Behavior survey. Physical abuse increased risk directly and indirectly through reduced self‐esteem. Involvement in youth programs moderated the direct effect. Community service moderated the indirect effect. Results indicate 2 hours per week of involvement in youth programs and 2 hours per week of community service mitigated suicide attempt risk associated with abuse. Providing avenues for youth experiencing abuse to increase their community service and involvement is recommended.